Association between Serum Adiponectin and Atrial Fibrillation: A Case-Control Study Stratified by Age and Gender - Tongjian Zhu; Zhuo Wang; Songyun Wang; Wei Hu; Hui Chen; Jing Xie; Meng Wang; Kezhong Ma; Hong Jiang (Cardiology Research and Practice)
Background. Circulating adiponectin has been suggested to be associated with atrial fibrillation (AF). However, whether the association differs by age and gender remains unknown. We performed a case-control study to evaluate the above association. Methods. AF patients who underwent 24-hour long-range 12-channel electrocardiogram examination at our center were included in this study, and people with normal sinus rhythm (NSR) were included as controls. All participants underwent echocardiography and heart rate variability tests. Biochemical parameters and adiponectin levels were also evaluated. Receiver operating characteristic (ROC) analyses were used to determine the predictive efficacy of adiponectin for AF, and multivariate logistic regression analysis was performed to evaluate the potential independent predictors of AF. Results. Overall, 84 patients with AF and 84 people with NSR were included. Serum adiponectin was significantly higher in AF patients compared to that in controls (P<0.001). ROC analysis showed that higher serum adiponectin (>6.098 μg/mL) had predictive efficacy for AF, with an area under the curve of 0.660 (95% confidence interval [CI]: 577–0.742). The results of multivariate logistic regression analysis showed that higher adiponectin was an independent predictor of AF in the overall participants (odds ratio [OR] 1.224, 95% CI 1.018–1.471, P=0.032). Subgroup analysis showed that higher adiponectin was independently associated with AF in women (OR 1.893, 95% CI 1.160–3.089, P=0.011) and in patients aged < 65 years (OR 1.453, 95% CI 1.023–2.064, P=0.037), but not in men or those aged ≥ 65 years. Conclusions. Higher serum adiponectin level was independently associated with higher odds for AF in women and in participants <65 years old, but not in men or those aged ≥65 years.